Model Pembelajaran LAPS-Heuristic, Pengaruh ke Kemampuan Berpikir Reflektif Ditinjau dari Minat Belajar - Esy Widianti; Nila Kesumawati; Ety Septiati (Jurnal Pendidikan Matematika RAFA, 2019)
The purpose of this study was to determine the effect of the LAPS-Heuristic learning model on reflective thinking skills in terms of student learning interests. The method used in this study was a quasi-experimental method (quasi experiment), with design factorial (factorial design). This research was conducted at Middle School in Palembang. The sample of this study was class VII1 students as the experimental class and class VII2 students as the control class with conventional learning applied. Data analysis using Two Way Anava with a significance level of 5%. The results of this study concluded that: (1) There is the influence of the LAPS-Heuristic learning model on students' mathematical reflective thinking abilities. (2) There are differences in students 'mathematical reflective thinking skills towards students' learning interests. (3) There is no interaction between the learning model